Activity and selectivity of CO2 photoreduction on catalytic materials. Issue 37 (3rd September 2020) - Yin, Wen-Jin; Wen, Bo; Ge, Qingxia; Li, Xi-Bo; Teobaldi, Gilberto; Liu, Li-Min
Abstract : Photoreduction of molecular CO2 by solar light into added-value fuels or chemical feedstocks is an appealing strategy to simultaneously overcome environmental problems and energy challenges. Abstract : Photoreduction of molecular CO2 by solar light into added-value fuels or chemical feedstocks is an appealing strategy to simultaneously overcome environmental problems and energy challenges. However, multiple reaction steps and a large number of possible products have significantly hindered the development of highly selective catalysts capable of delivering CO2 conversion with high efficiency. Recently, several strategies associated with different conversion mechanisms have been proposed to improve the activity and product selectivity of CO2 photocatalysts. These are based on development of low dimensional nanomaterials, defect or facet engineering, design of tailored heterostructures, and carrier conductivity enhancement. In spite of impressive progress in the field, real-world applications are yet to be delivered. To sustain further research in this promising field, here we provide a short frontier of recent advances in activity and selectivity of CO2 reduction photocatalysts, together with a critical discussion of further avenues of research in this field.